A newly-recorded species of the genus Ablemma Roewer, 1963 (Araneae, Tetrablemmidae) from China - Hongjin Fu; Yuzhu Wang; Yanfeng Tong (Biodiversity Data Journal, 2022)
Ablemma Roewer, 1963 is a species-rich genus of the family Tetrablemmidae O. Pickard-Cambridge, 1873, currently comprising 28 known species. This genus is mainly distributed in Southeast Asia. Currently, only one species, A. prominens Tong & Li, 2008 is known to occur in China.The species Ablemma shimojanai (Komatsu, 1968), presently only known from the Ryuku Islands in Japan, is reported from China for the first time on the basis of material collected in Guangdong Province. A morphological description and detailed images are provided.